School for Mentally Retarded Online System / Amer Imran Kamaruzaman - Amer Imran, Kamaruzaman (2003)
Most of the school for mentally retarded are still using the old manual filing system or a semi-computerized system. In order to keep up with the computer era today, an online system is needed in order to manage the schools efficiently and systematically. Realizing the potential and the need of a new system, I have decided to develop this School for Mentally Retarded Online System. This system is a combination of web based and client-server architecture application system. Users of this system are able to access this system online. The system is developed using Active Server Pages 3.0 (ASP) technologies, SQL Server 7.0, as well as VBScript. This system is developed with intention to replace the existing manual system to a new computerized online system. Using this system will improve the way of managing the schools and hopefully the system will be beneficial to everyone.